(354) بعض المسائل العامة التي سيعالجها مؤتمر التجارة الدولية Some general issues that will be addressed by the International Trade Conference - ابراهيم حلمي عبد الرحمن (معهد التخطيط القومي, 2026)
ملخص تتناول هذه المذكرة البحثية التي أعدها الدكتور إبراهيم حلمي عبد الرحمن عام ١٩٦٣ تحليلاً استشرافياً للمسائل الجوهرية التي عالجها مؤتمر التجارة الدولية، مبرزةً الاعتراف العام بأن شروط التبادل التجاري العالمي باتت تميل بشكل حاد ضد مصالح الدول النامية نتيجة تقلبات أسعار المواد الأولية وحواجز الأسواق المتقدمة. وتستعرض الدراسة حزمة من الحلول الاقتصادية المقترحة، منها إقرار نظم للتمويل التعويضي وتعديل قواعد منظمة "الجات" لتشمل مزايا تفضيلية للسلع المصنعة من الدول الناشئة، مع مناقشة البدائل المؤسسية لإنشاء منظمة تجارة دولية جديدة توازن بين القوى الاقتصادية الكبرى واحتياجات التنمية في العالم الثالث. وتخلص المذكرة إلى أن نجاح الدول النامية في تحسين واقعها الاقتصادي يتوقف جذرياً على قدرتها على صياغة موقف موحد و"كتلة" تفاوضية قوية تجاه القضايا الكلية للمؤتمر، بدلاً من الانخراط في حلول ثنائية جزئية تضعف كلمتها الدولية. وتؤكد الرؤية المطروحة أن معالجة فجوة الدخل ومستوى المعيشة بين الشمال والجنوب تتطلب إرادة سياسية من الدول المتقدمة لإجراء تغييرات هيكلية في النظام النقدي والتجاري العالمي، مما يضمن تحويل التجارة الدولية من أداة لاستنزاف الموارد إلى محرك حقيقي للتنمية الشاملة والرفاهية المشتركة. This research paper, prepared by Dr. Ibrahim Helmy Abdel Rahman in 1963, offers a forward-looking analysis of the core issues addressed by the International Trade Conference. It highlights the general recognition that the terms of global trade were increasingly tilted against the interests of developing countries due to fluctuating raw material prices and barriers in developed markets. The study presents a range of proposed economic solutions, including the establishment of compensatory financing mechanisms and the amendment of the GATT rules to include preferential treatment for manufactured goods from emerging economies. It also discusses institutional alternatives for creating a new international trade organization that balances the interests of major economic powers with the development needs of the Third World . The memorandum concludes that the success of developing countries in improving their economic situation fundamentally depends on their ability to formulate a unified position and a strong negotiating bloc on the overarching issues of the conference, rather than engaging in partial bilateral solutions that weaken their international voice. The proposed vision emphasizes that addressing the income and living standards gap between the North and the South requires political will from developed countries to implement structural changes in the global monetary and trade system, ensuring that international trade is transformed from a tool for resource depletion into a genuine engine for inclusive development and shared prosperity .